Biostatistics for the biological and health sciences - Triola, Marc M.; Trola, Mario F.; Roy, Jason (Pearson Education Limited, 2019)
Biostatistics for the Biological and Health Sciences uses a variety of real-world applications to bring statistical theories and methods to life. Through these examples and a friendly writing style, the 2nd Edition ensures that students understand concepts and develop skills in critical thinking, technology, and communication. The result of collaboration between two biological sciences experts and the author of the #1 statistics book in the US, Biostatistics for the Biological and Health Sciences provides an excellent introduction to statistics for students studying the biological, life, medical, and health sciences.